Exercises in Travel Writing and Literary Tourism: A Teaching and Learning Experiment (University of Maribor Press, 2020)
The book entitled »Exercises in Travel Writing and Literary Tourism – A Teaching and Learning Experiment« emerged as a result of experimental project work in teaching English during the subject English in Tourism – Higher Level 1 at the Faculty of Tourism in Brežice, University of Maribor. This approach included teaching in the classroom, research in libraries and at home, and field work. The collection brings eight very different texts on Travel Writing and Literary Tourism by Master’s students of Tourism, who were free in choosing the topic of the texts, their styles and the titles . The field of Travel Writing is significant, not only as its own discourse, a tourism trend and a tool of branding and embedding attractions and/or destinations, but also as a tool of teaching and learning a foreign language, which, along with upgrading specific language knowledge, encourages curiosity, research, creativity, reflection and self-development.